2022
DOI: 10.55299/ijphe.v1i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Papaya Decoction (Papaya Carica L.) on Increasing Breast Milk Production in Breastfeeding Mothers

Abstract: Breastfeeding in postpartum mothers often encounter obstacles due to late release of breast milk or less milk production. Efforts to improve the nutrition of nursing mothers by providing nutrient-rich foods that can stimulate milk production, namely papaya fruit stew. This study aims to determine the effect of boiled papaya on increasing breast milk production. This research was conducted at the Independent Midwife Nelly Harahap Panyanggar, North Padangsidimpuan District on 27 breastfeeding mothers. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Papaya ( Carica papaya L) is a simplicia that can increase the bulk of breast milk secretion. Pebrianthy et al [ 36 ] stated that giving papaya leaf decoction is an effort to improve nutrition for breastfeeding mothers. Research conducted on 27 breastfeeding mothers in Padangsidempuan showed that papaya stew affected increasing milk production in nursing mothers ( p -value = 0.001, ( p < 0.05)) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Papaya ( Carica papaya L) is a simplicia that can increase the bulk of breast milk secretion. Pebrianthy et al [ 36 ] stated that giving papaya leaf decoction is an effort to improve nutrition for breastfeeding mothers. Research conducted on 27 breastfeeding mothers in Padangsidempuan showed that papaya stew affected increasing milk production in nursing mothers ( p -value = 0.001, ( p < 0.05)) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%